Karakteristik Sensorik Ikan Gulamah (Pseudocienna Amovensis) pada Kadar Garam yang Berbeda - Jaulim Sirait; Wahyu P Ariyadi; Simson Masengi; Yuliati H Sipahutar; Aghitia Maulani (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2022)
Processed salted fish products are still aimed at extending shelf life and have not considered the need for sensory, chemical and microbiological quality. The final quality of salted fish processing is very diverse, depending on the amount of salt used. Gulamah fish (Pseudocienna amovensis) is one of the abundant types of fish and is the main raw material for salted fish processing in Tangerang Regency. This study used a salt content of 10%, 15%, 20% and 25%. Sensory assessment using 30 panelists. The method of analysis used the Kruskal Wallis test. The results of sensory analysis with the addition of 10%, 15%, 20% and 25% salt content, gave the appearance value of 6.9; 7.7; 8.6; 8.1, smell 7.7; 8.4; 8.7; 7.5, and textures 7.1; 7.5; 8.1; and 8.5. The results showed that the amount of salt had a significant effect on appearance, taste and texture, but had no effect on odor. The results showed that increasing salt content could increase the sensory value of salted fish.